Создание безбарьерной образовательной среды при социализации ребёнка с ОВЗ в общество здоровых детей - Diomina S. I. (Образовательная среда сегодня: стратегии развития, 2015)
the educational institution is obliged to create conditions for a child with special needs, promoting socialization, providing equality of opportunity, full participation in society, the right to education and social protection, emotional well-being.
Keywords: ФГОС ДО; безбарьерная образовательная среда; Prior TO GEF; barrier-free learning environment